2008
DOI: 10.1507/endocrj.k07e-010
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Benign and Malignant Tumors in Patients with Acromegaly at a Single Institute

Abstract: Abstract. It has been reported that patients with acromegaly may have an increased risk of developing several types of cancers, such as colorectal, breast and prostate tumors. However, some reports do not support these findings and therefore the prevalence of cancers in patients with acromegaly remains controversial. In this study, we determined the prevalence of benign and malignant neoplasms in patients with acromegaly. A retrospective chart analysis was performed on 140 patients with active acromegaly who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
2
13

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 22 publications
5
42
2
13
Order By: Relevance
“…In one study, the rate of colonic lesions was 51.7%, and 10.3% of it was colon carcinoma [19]. In our study, the colonic lesion prevalence was observed as 30.2%, and no carcinoma was found.…”
Section: Discussionsupporting
confidence: 49%
“…In one study, the rate of colonic lesions was 51.7%, and 10.3% of it was colon carcinoma [19]. In our study, the colonic lesion prevalence was observed as 30.2%, and no carcinoma was found.…”
Section: Discussionsupporting
confidence: 49%
“…Studies suggest that acromegalic patients present higher risk of developing both benign and malignant tumors including the ones that affect the gastrointestinal tract, thyroid, and skin (6,7). The correlation between acromegaly and prostate cancer, until the present moment, is circumstantial.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that acromegaly is associated with an increased prevalence of colorectal, breast, prostate and thyroid cancers, as determined in several epidemiological studies (1)(2)(3). However, it is currently unclear whether patients with acromegaly are at an increased risk of developing adrenal tumors.…”
Section: Introductionmentioning
confidence: 99%